Augmented Reality Application in Malaysia Multimedia Super Corridor (Government Electronic, Smart School and Smart Card) - Ali, Azita; Shahnam, Mohamad Hazim Aiman (Research and Innovation in Technical and Vocational Education and Training, 2022)
The project aims to design and develop an Augmented Reality Application in Malaysia Multimedia Super Corridor (Government Electronic, Smart School and Smart Card). Augmented Reality technology was chosen because of its potential to affect education in the teaching and learning processes positively. Augmented Reality application development can help society particularly students gain exposure and awareness in comprehending three major fields of MSC applications provided by the government to advance the nation and people globally. The model used in the development of this product is the Hannafin and Peck which includes three main phases namely need assessment, design and development or implementation. Each phase will go through the evaluation and revision. The analysis phase was conducted by analysing past cases to find out the problem. In the design phase of the product, the developer creates the storyboard and get feedback from the design content and interface specialist. In the development or implementation phase, the developer creates a prototype using selected hardware and software. The evaluations carried out by five (5) specialists in a creative multimedia field from the Faculty of Technical and Vocational Education (FPTV). Three (3) specialists were chosen in evaluating design content while two (2) specialists in design interface for the development of Augmented Reality application. The instrument of study used is the expert checklist form. Data are analysed using the frequency and percentage method. The findings of the study found out that all five specialists gave a positive response to this product. The results obtained by this product can help society, especially students to gain a better understanding of the three MSC branches introduced by the government.